Perlindungan Hukum Terhadap Penerima Bilyet Giro Kosong - Dwi Arina Fahrun Nisa; Widya Elfareda Putri; Sumriyah Sumriyah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Legal protection of recipients of empty bilyet giro is important in maintaining trust and stability in the banking system. An empty bilyet giro is a bilyet giro submitted to the bank, but the customer’s funds at the bank are insufficient to pay or fulfill the order on the bilyet giro concerned. However, when the bilyet giro is issued without sufficient funds, the recipient of the empty bilyet giro can be at risk of loss. The purpose of this study is to analyze the existing legal protection for recipients of empty bilyet giro and find solutions in overcoming problems arising from the use of empty bilyet giro. The method used in this research is a type of normative juridical research, which is a research carried out by examining laws and regulations that regulate legal protection issues for bilyet giro holders. To improve legal protection for recipients of empty bilyet giro, it is recommended to improve banking regulations governing the procedure for issuance and use of empty bilyet giro. And arrangements on legal protection of holders of empty bilyet giro so that holders of empty bilyet giro are not disadvantaged in trading because he does not obtain what is rightfully his.